Pengaruh Aktivitas Social Media Marketing Terhadap Brand Trust, Brand Equity, dan Brand Loyalty Pada Platform Social Media Instagram - Irawan, Alfian Dally; Hadisumarto, Aswin (UI Scholars Hub, 2020)
This study aims to determine the effect of social media marketing activities as seen from the dimen- sions of entertainment, interaction, trendiness, customization, and word-of-mouth, on brand trust, brand equity and brand loyalty conducted by Instagram social media. The study uses the Structural Equation Modeling (SEM) method with a sample of 617 respondents who are Indonesian residents ranging in age from 17 to 35 years and have used Instagram social media for a minimum of six months. The results showed that social media marketing activities viewed based on entertainment, interaction, trendiness, customization, and word-of-mouth had a positive effect on brand trust, brand equity, and brand loyalty. Furthermore, brand trust has a positive influence in mediating social media marketing activities on brand equity and brand loyalty, and brand equity also has a positive influence in mediating social media market activities on brand loyalty.